2015
DOI: 10.1039/c5ra11772k
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of ultra-small ruthenium oxide nanoparticles anchored on reduced graphene oxide nanosheets for high-performance supercapacitors

Abstract: Herein, we report a facile, low cost, and environmentally friendly approach to prepare reduced graphene oxide-ruthenium oxide hybrid (RGO-RuO2) materials for supercapacitor electrode applications by in situ sol-gel deposition of RuO2 nanoparticles on the surface of graphene oxide (GO), followed by a reduction of GO in a strong alkaline medium at a low temperature. The combination of the sol-gel route and the reduction of graphene oxide at low temperature resulted in ultrafine, hydrated amorphous RuO2 particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Herein, hydrated amorphous RuO 2 particles with 1.0–2.0 nm dimensions were homogeneously decorated on the surfaces of rGO sheets. The gravimetric capacitance of 500 F g −1 was acquired in 1 M H 2 SO 4 electrolyte at 1.0 A g −1 current density with capacitance retention ∼87 % after 2000 cycles …”
Section: Ruo2‐based Nanocomposites and Their Electrochemical Featuresmentioning
confidence: 99%
“…Herein, hydrated amorphous RuO 2 particles with 1.0–2.0 nm dimensions were homogeneously decorated on the surfaces of rGO sheets. The gravimetric capacitance of 500 F g −1 was acquired in 1 M H 2 SO 4 electrolyte at 1.0 A g −1 current density with capacitance retention ∼87 % after 2000 cycles …”
Section: Ruo2‐based Nanocomposites and Their Electrochemical Featuresmentioning
confidence: 99%
“…Graphene oxide (GO) was prepared by the modified Hummers method, using expanded graphite as the starting material [15]. The as-prepared GO was diluted to a concentration to 2.0 mg mL -1 and sonicated for 30 min.…”
Section: Preparation Of Hrgo-ruomentioning
confidence: 99%
“…The subsequently fabricated supercapacitor exhibited excellent electrochemical capacitive properties [15]. In another recent study, Xu et al [13] reported a scalable, defect-etching strategy to improve the surface area and mass diffusion rate of RGO by creating nanopores across the entire basal plane of the RGO sheets.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the irregular size ands egregation of multilayered MXeneb locks make them lose or disconnect the electrical contactb etween them during charge/discharge. [3,[7][8][9][13][14][15][16][17][18][19] The combination of MXene with alien materials such as 0D transition metal oxidesT MOs, [22,32,33] 1D carbon nanotubes (CNTs), [15] 2D reduced graphene oxide (rGO) nanosheets, [20,21,34,36] or the polymers polyaniline (PANI), polyvinyl alcohol (PVA), poly(diallyldimethylammonium) chloride (PDDA), and PPy [16,35,37] to form composites hasb een applied to preventt he restacking. Recent advances have demonstrated that the electrochemical performancesd epends trongly on the nanostructure of the electrode materials.…”
Section: Introductionmentioning
confidence: 99%